2017
DOI: 10.1016/j.resuscitation.2016.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes from out-of-hospital cardiac arrests in England

Abstract: Introduction: This study reports the epidemiology and outcomes from out-of-hospital

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
184
6
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 277 publications
(226 citation statements)
references
References 28 publications
13
184
6
12
Order By: Relevance
“…The incidence of OHCA was comparable to other countries such as England (53), North America (56) and Denmark (62) . Also similar to international services such as England, the proportion of OHCA occurring in males was higher than that of females …”
Section: Discussionsupporting
confidence: 68%
“…The incidence of OHCA was comparable to other countries such as England (53), North America (56) and Denmark (62) . Also similar to international services such as England, the proportion of OHCA occurring in males was higher than that of females …”
Section: Discussionsupporting
confidence: 68%
“…A systematic review of cardiac arrest randomised controlled trials published between 2002 and 2012 identified 61 trials, of which only three (5%) included in-hospital cardiac arrest patients [29]. Differences between out-of-hospital and in-hospital cardiac arrest in terms of patient characteristics and clinical response limit the direct generalisability of research findings between these settings [1, 30]. Furthermore, it likely means that experience and lessons learned from the successful delivery of out-of-hospital cardiac arrest research cannot necessarily be directly transferred to the in-hospital setting [31].…”
Section: Discussionmentioning
confidence: 99%
“…un-witnessed cardiac arrest, no bystander CPR for more than 15 minutes, asystolic rhythm and absence of a potentially reversible cause (e.g. hypothermia)) may lead to resuscitation being withheld (27). In other countries resuscitation would be provided in such circumstances (28).…”
Section: Smart Technologies For Activation Of Lay Respondersmentioning
confidence: 99%